Representasi Makna Kehilangan dalam Film "Racun Sangga: Santet Pemisah Rumah Tangga" - Yosua, Richard; Mareta Puri Rahastine (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
This research analyzes the representation of the meaning of loss in the Indonesian horror film, Racun Sangga: Santet Pemisah Rumah Tangga. Loss in this context is found to be multidimensional, covering the loss of love, harmony, and self-identity within a domestic setting influenced by mysticism and patriarchal structures. The research objective is to analyze how the meaning of loss is constructed and visually represented in the film's narrative. The study employs a qualitative approach using Roland Barthes' Semiotic Analysis (denotation, connotation, myth), framed within Stuart Hall's Representation Theory. The focus is on the film Racun Sangga, addressing issues of trauma and women's resistance. The analysis results indicate that loss is constructed as complex trauma, involving emotional devastation and social alienation. This is visualized through key symbols such as the broken mirror and the santet (black magic) doll. The findings also reveal ambiguous gender relations: while women are victims of patriarchy, the santet practice is used as a symbolic strategy of resistance to seek justice outside of the oppressive formal system. In conclusion, Racun Sangga functions as a cultural text that actively constructs a discourse on trauma, power, and spirituality in a society still shaped by mystical values.   Keywords: Representation, Loss, Film, Semiotics, Santet, Trauma.